The Concept of Dressing for Muslim Women from the Al-Qur'an Perspective: A Study of Maqasidi's Tafsir - Soviatus Salamah; Eka Prasetiawati; Muhammad Nur Amin (al-Afkar, Journal For Islamic Studies, 2026)
This study aims to examine the concept of Muslim women's attire from the perspective of the Qur’an, utilizing a maqasidi exegesis (tafsir) approach. It is motivated by rapid technological advancements in the modern era that have influenced the fashion world, leading to a shift in the orientation of Muslim women's clothing one that increasingly prioritizes aesthetics and style over Sharia values. The study employs a qualitative method based on library research to gain a comprehensive understanding of the Qur’anic concept of Muslim women's attire. The findings indicate that this concept is not merely focused on physical aspects but also encompasses normative dimensions reflecting moral and spiritual values. These principles include the obligation to cover the awrah (intimate parts of the body), the use of loose-fitting and non-transparent clothing, the maintenance of modesty, and the avoidance of imitating the opposite sex. From the perspective of maqasidi exegesis, these dress guidelines reflect comprehensive Sharia objectives namely the preservation of religion (hifz al-din), life (hifz al-nafs), and lineage (hifz al-nasl) serving both protective and preventive functions in safeguarding individual honor and social stability.